Multidisciplinary Evaluation of Pacifier Removal on Oro-Dentofacial Structures: A Controlled Clinical Trial - Scudine, Kelly Guedes de Oliveira; Freitas, Camila Nobre de; Nascimento de Moraes, Kizzy Silva Germano; Bommarito, Silvana; Possobon, Rosana de Fátima; Boni, Rosana Cristina; Castelo, Paula Midori (Frontiers in Pediatrics, 2021)
It is well recognized that pacifier habit leads to occlusal and orofacial functional changes in children. However, the effects of the interruption of prolonged pacifier habit on the development of the dento-facial complex has not yet been fully characterized. Thus, the aim of this study was to investigate the influence of pacifier removal on aspects of oro-dentofacial morphology and function in preschool children. For that, a pacifier group (n=28) and a control group (n=32) of 4-year-old children with and without pacifier habit, respectively, were followed up by a group of dentists and speech therapists at baseline, 6 and 12 months after habit removal. Bite force and lip pressure were assessed using digital systems, and the evaluation of breathing and speech functions was performed using validated protocols, together with the measurements of dental casts and facial anthropometry. The Two-way mixed model ANOVA was used in data analysis. After 12 months, a decrease in malocclusion frequency was observed in pacifier group. Additionally, a change over time was observed in facial, intermolar and palate depth measurements, as well in bite and lip forces and speech function scores, increasing in both groups (p<0.01). The upper and lower intercanine widths and breathing scores differed between groups at baseline and changed over time reducing the differences. The presence of speech distortions was more frequent in the pacifier group at baseline and decreased over time (p<0.05). The interruption of pacifier habit improved the maxillary and mandibular intercanine widths, as well as the breathing and speech functions, overcoming the oro-dentofacial changes found. Trial Registration: This clinical trial was registered in the Brazilian Clinical Trials Registry (ReBEC; http://www.ensaiosclinicos.gov.br/), protocol no. RBR-728MJ2.